Deficiencias en la (re)construcción constitucional del proceso de habeas data en el Perú - Loyola Ríos, Néstor (2025)
In this article, the author analyzes the shortcomings in the constitutional reconstruction of the habeas data process in Peru, focusing on the protection of the right of access to public information and informational self-determination. Through a review of the regulatory framework and its evolution, the article highlights the challenges in implementing the process established in the New Constitutional Procedural Code. Despite the reforms, the article points out technical and procedural flaws that make it difficult for both citizens and justice officials to understand. Furthermore, regulatory adjustments are proposed that could improve the effectiveness of this constitutional process, especially in relation to the mandatory nature of legal representation, the definitions of personal data banks, and the lack of alignment between administrative and jurisdictional regulations. The author concludes that it is urgent to modify the current legislation to facilitate access to justice and guarantee the protection of citizens’ fundamental rights.